UKRAINIAN AGRICULTURAL COOPERATION IN THE BACKGROUND OF THE REVOLUTIONARY CONSUMPTION OF THE EARLY 20TH CENTURY - Morozov, A.; Pavlova, N. (Ukrainian Peasant, 2019)
The article reveals the regularities and peculiarities of the development of Ukrainian agricultural cooperation during the first two decades of the twentieth century. The contribution of domestic theorists and practitioners of co operation, as well as the role of All-Ukrainian Congresses of Cooperation and the Provisional Central Ukrainian Cooperative Committee was shown. The influence of the revolutionary times of 1905 – 1907 and 1917 – 1921, as well as the First World War on the dynamics and directions of the cooperative movement was determined.